ANALISIS FAKTOR UNTUK MENGIDENTIFIKASI FAKTOR KETERLAMBATAN PADA PEKERJAAN GEDUNG BERTINGKAT - Julia Damayanti; Dewi Rintawati (Universitas Trisakti, 2019)
Successfully executing construction project within schedule is one of the most important aim, both from project owner and contractor’s point of view. Construction delay is a condition which is completely unwanted, as it will cause lost of money and time for both parties. This study was conducted to determine factors that most likely cause delays at the onset of the project. As many as 42 (forty two) variables have been identified as causing a delay claim based on the study of various literature. This is subsequently tested in the form of questionnaire or survey distributed to employers and contractors involved in the project, across different working levels of staff. Through factor analysis method using SPSS software, 7 (seven) factors have been further identified as main causes of delay claims in construction project. .